LAW AS A COMPLEX ADAPTIVE SYSTEM: PATH TOWARD SELF-SUSTAINABILITY OF LEGAL FRAMEWORK - Cvetković, Predrag (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The topic of the paper is the possible implementation of the Complex Adaptive Systems (CAS) concept in the field of law. The CAS concept rests on the existence of a dynamic network with many actors (individuals, companies, states, international institutions), acting simultaneously and constantly responding to the behavior of other actors in the network. The Complex Adaptive System is based on connections that are generated by gradual induction of certain rules; thus, the newly established order is not conditioned by a superior authority, but it functions as a self-regulated one. The CAS concept is not hierarchical, but heterarchical. Unlike the hierarchical structure, heterarchy is a structure that rests on a number of centers of equal standing in the system. The heterarhical system does not rest on the premise of fundamental unity, universal interests, and alike (as common features of the hierarchical system). Instead, the heterarchical system generates rules that cannot be observed and analyzed separately from the application process. The ability of actors or agents to respond to new challenges determines the adaptive character of this system. Applied to the field of law, the CAS concept is especially important when the legal situation at stake is prone to the change of the fundamentals on which it was based at the outset. The actors of the legal relationship (viewed as part of the CAS network) define mutual relations on the basis of the acquired experience resulting from the operation of the particular system. The Complex Adaptive System has tendency to retain patterns that have proved to be adequate and usable for a further process of self-construction of the order in the system. The factors driving and enabling the connection within the elements of “law-oriented” complex adaptive systems are embodied in common values, principles and methods of interpretation. The paper illustrates the application of the CAS concept by providing the example of convergence among the agreements from the field of Foreign Investments Law (FIL).